Susteinability in contemporary gastronomy (Research, Society and Development, 2021)
The concern with quality food combined with the care of the environment has grown over the years. The objective was to carry out a bibliographic review, aiming to discuss the data obtained in several articles, on sustainability in contemporary gastronomy. The methodology used was a bibliographic search, gathering scientific articles, books, course conclusion papers and academic theses related to sustainable contemporary gastronomy, published between 2001 and 2021 in English and Portuguese. In many cases, an alliance was observed between chefs, diners and producers, for example for the insertion of family farming products in the diet. It was concluded that the awareness of sustainability in contemporary gastronomy causes improvements not only in the development and local sustainability, but also in the sensorial quality of food, much higher than that of industrialized products.